Open access to scholarly communications: advantages, policy and advocacy - FURNIVAL, Ariadne Chloe (2010)
The Open Access (OA) movement regards OA modes of disseminating research as the unequivocal future of scholarly communication. Proponents of the open access movement itself have, over the last ten years, carried out systematic research to show how OA can tangibly benefit researchers, institutions and society at large. Even so, the number of research papers being uploaded to OA institutional repositories remains relatively low, frequently based on concerns which often contradict the facts. Policies for OA have been introduced to encourage author uptake, and these are also discussed here. Briefly delineating aspects of these phenomena, this paper will then move on to outline and discuss advocacy for OA in organisations, and whether this should be “downstream”, in the form of informational campaigns, or “upstream”, in the form of top-down change management. This paper seeks to make a contribution to these issues in the OA sphere, by brining into the debate strands from the literature of the sociology of science and management science that will hopefully elucidate aspects of author reactions to OA, and the perceived changes that its adoption gives rise to.